Russia and the Balkans : inter-Balkan rivalries and Russian foreign policy, 1908-1914 - Rossos, Andrew, 1941- (University of Toronto Press, 1981)
This volume presents an objective diplomatic history focused on five crucial years in the relations between Russia and the Balkan states from the Annexation Crisis of 1908-9 to the outbreak of the First World War.